2012
DOI: 10.1007/s12031-012-9829-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Induces Epigenetic Modulation of Prodynorphin and Pronociceptin Gene Expression in the Rat Amygdala Complex

Abstract: Several studies demonstrated the role of the endogenous opioid system in the development of susceptibility to alcohol dependence. Recently, we reported that binge intragastric administration of ethanol induces selective alterations of pronociceptin and prodynorphin gene expression in the rat amygdala complex depending on the days of exposures and on the development of tolerance and dependence. The aim of the present study was to investigate the potential epigenetic mechanisms leading to these alcohol-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…Tissue-and gene-specific DNAm alterations were identified by one study in folate-regulating genes [27]. Finally, no associations were found in opioid-related genes Pdny and Pnoc in the rat amygdala [28], as well as imprinting-control genes H19 and Rasgfl in mouse sperm [14].…”
Section: Adulthoodmentioning
confidence: 97%
See 1 more Smart Citation
“…Tissue-and gene-specific DNAm alterations were identified by one study in folate-regulating genes [27]. Finally, no associations were found in opioid-related genes Pdny and Pnoc in the rat amygdala [28], as well as imprinting-control genes H19 and Rasgfl in mouse sperm [14].…”
Section: Adulthoodmentioning
confidence: 97%
“…Furthermore, hypermethylation of the serotonin receptor 3A (HTR3A) was identified in relation to alcohol exposure across both humans [42] and rodents [23]. Finally, a null association between alcohol exposure and methylation in the opioid signaling genes PDNY and PNOC was reported in human blood [42] and brain tissue in rats [28]. Despite these consistent findings, it is noteworthy that genes investigated by candidate studies did not typically converge with those identified by studies using hypothesis-free, epigenome-wide analyses.…”
Section: Summary Of Study Characteristics and Findingsmentioning
confidence: 99%
“…Studies of patients with alcohol dependence have identified ethanol-induced changes to histone modifications in the brain (Zhou et al, 2011; Ponomarev et al, 2012). In the rat amygdala, acute ethanol increases global and prodynorphin and pronociceptin promoter histone acetylation levels (Pandey et al, 2008; D’Addario et al, 2013), and reduces prodynophin and pronociceptin H3K27me3 binding (D’Addario et al, 2013). Moreover, in the hippocampus, ethanol-induced histone H3 acetylation and H3K4me3 have been found to regulate expression of brain derived neurotrophic factor (BDNF) exons (Stragier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence showing that activation of κ opioid receptor produces depressive-like disorders in human and rodents [12][13][14][15][16][17][18][19], whereas blockade of κ opioid receptor produces antidepressive-like effects [20][21][22][23]. Chronic exposure to cocaine, morphine, heroin and alcohol have been shown to be associated with increased dynorphins expression in different brain regions, such as striatum, NAc and amygdala, and potentiated endogenous signaling through κ opioid receptor [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%